1994
DOI: 10.1007/bf02365444
|View full text |Cite
|
Sign up to set email alerts
|

Serum trace metals in chronic viral hepatitis and hepatocellular carcinoma in Thailand

Abstract: This study was conducted to determine and compare serum trace metal levels in viral hepatitis-associated chronic liver disease. Of 98 patients aged 43 (+/- 13) [mean (+/- SD)] years, 83 (85%) were seropositive for hepatitis B surface antigen (HBsAg) and 15 (15%) were seropositive for anti-hepatitis C virus (HCV). Twenty-five patients had chronic persistent hepatitis, 32 chronic active hepatitis, 21 post-necrotic cirrhosis, and 20 hepatocellular carcinoma. Determination of fasting serum trace metal levels (zinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
1
4

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 25 publications
(2 reference statements)
4
30
1
4
Order By: Relevance
“…4,[42][43][44][45] To assess this zinc relationship, one must recognize that homeostatic physiological mechanisms regulate and maintain a constant normal plasma zinc concentration, which is ~12-15 uM in humans. The plasma zinc concentration is maintained basically by the balance of dietary zinc intestinal absorption and assimilation into blood, the distribution of zinc among the tissues of the body, and the "excretion" of zinc out of the body.…”
Section: The Implication Of Zinc In the Predisposition Of Hcc Developmentioning
confidence: 99%
“…4,[42][43][44][45] To assess this zinc relationship, one must recognize that homeostatic physiological mechanisms regulate and maintain a constant normal plasma zinc concentration, which is ~12-15 uM in humans. The plasma zinc concentration is maintained basically by the balance of dietary zinc intestinal absorption and assimilation into blood, the distribution of zinc among the tissues of the body, and the "excretion" of zinc out of the body.…”
Section: The Implication Of Zinc In the Predisposition Of Hcc Developmentioning
confidence: 99%
“…Several small studies have evaluated serum zinc levels in patients with chronic viral hepatitis. [69][70][71][72][73][74] The results have been mixed. Three found no significant differences when compared with controls; however, others have demonstrated a signifi-cant decrease in serum zinc levels when compared with controls.…”
Section: Zinc In Viral Hepatitismentioning
confidence: 99%
“…Three found no significant differences when compared with controls; however, others have demonstrated a signifi-cant decrease in serum zinc levels when compared with controls. [69][70][71][72][73][74] In one of these studies, a significant difference was found only in those patients with cirrhosis. 72 Another of these studies only looked at patients with chronic hepatitis C and demonstrated that, in addition to lower serum zinc levels at baseline, these reductions were exacerbated further following injection of INF-α.…”
Section: Zinc In Viral Hepatitismentioning
confidence: 99%
“…The essential micronutrients (Zn, Cu, Fe, and Se) might exacerbate liver disease in case of deficiency, imbalance, or toxicity [5,30] . They are also linked to the process of oxidation during chronic liver damage [6,7,31] . In the present investigation, the levels of Zn and Se in plasma and erythrocytes of HCV-infected patients decreased significantly compared to healthy subjects.…”
Section: Correlation Of Micronutrient Concentrations With Hcv-rna Levelsmentioning
confidence: 99%
“…Decreasing levels of Zn, Se, or increasing Cu levels were also noted in sera of hepatitis cases [31][32][33] . HCV-and HIV-coinfected patients showed markedly lower blood Se levels compared to HIV-infected patients without concomitant HCV infection [34] .…”
Section: Correlation Of Micronutrient Concentrations With Hcv-rna Levelsmentioning
confidence: 99%